Modeling and Analysis of Disc Brake Performance - Hafifi bin Mohd Yusop, Hafifi (Universiti Teknologi Petronas, 2008)
The project will employ basically using the method of simulation in ANSYS software, which is software used to analyze both structural and material non-linearity for engineering simulation. The data are gathered from trusted resources such as from internet, books, journal and dissertation thesis to be used in simulation using the ANSYS software. The result from the simulation using the detail in Proton Waja‟s disc brake will be a reference to improve the design.